A process for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding.
By combining polymer diffusion welding with handheld laser welding, and utilizing nano-Ag diffusion layers and Sc microalloy laser reinforcement, the welding gap and durability issues of aluminum-aluminum lap joints are solved, achieving low resistance, high strength and excellent fatigue resistance, which is suitable for electric vehicle battery module connections.
Patent Information
- Application Number
- CN202511171904.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-21
- Publication Date
- 2025-11-14
- Estimated Expiration
- 2045-08-21
AI Technical Summary
The welding quality of aluminum-aluminum lap joints has problems such as micropores and incomplete fusion gaps, which leads to increased contact resistance and energy consumption. Traditional polymer diffusion welding is prone to wear, and handheld laser welding has unstable energy coupling.
A combined process of polymer diffusion welding and handheld laser welding is adopted. An atomic-level conductive path is constructed through a nano-Ag diffusion layer, combined with Sc microalloy laser reinforcement, to form a stable diffusion layer and control welding parameters in real time, thereby eliminating gaps and improving durability.
This technology achieves low resistance, high strength, and excellent fatigue resistance in aluminum-aluminum lap joints, reduces welding defect rate and heat input fluctuation, and improves the conductivity and durability of the welded parts.
Smart Images

Figure CN120715400B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of welding technology, specifically a process method for welding aluminum-aluminum lap joints by combining polymer diffusion welding and handheld laser welding. Background Technology
[0002] Polymer diffusion welding is a solid-state joining technology. It involves pre-applying a composite flux containing an organic carrier to the welding interface. Under high temperature and pressure, the polymers in the flux decompose to form an active atmosphere, promoting metal atom diffusion and achieving a meltless metallurgical bond. This method is particularly suitable for large-area lap joints of easily oxidized metals such as aluminum. Handheld laser welding is a fusion welding process that uses a portable laser device to generate a high-energy-density beam to locally melt the base material. An alloy welding wire is simultaneously fed in to fill the weld seam. Dynamic zoom and real-time resistance feedback control the behavior of the molten pool, offering both operational flexibility and precise heat input control. It is often used for localized reinforcement of complex structures. The former relies on solid-state diffusion (no liquid phase), while the latter involves molten solidification. Polymer diffusion welding requires specialized hot-pressing equipment to achieve uniform pressure, while handheld laser welding relies on manual movement to complete the welding path.
[0003] In the field of aluminum welding, the welding quality of aluminum-aluminum lap joints has always been a technical challenge. While traditional polymer diffusion welding can achieve welding, it easily leaves micropores at the interface. After prolonged high-load operation, fretting wear occurs, leading to increased contact resistance and posing a risk of localized overheating in electric vehicle battery module connectors. On the other hand, when using handheld laser welding alone, the high reflectivity of aluminum causes unstable energy coupling, easily resulting in gaps between the welded parts, reducing the conductive cross-sectional area by more than 30%, leading to increased high-voltage busbar resistance and higher overall vehicle energy consumption. In view of these problems, this invention proposes a process method for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding. This method constructs atomic-level conductive pathways through a nano-Ag diffusion layer, combined with Sc microalloy laser reinforcement to achieve fatigue-resistant connections. This solves the gap problem between the welded parts and improves the durability and conductivity of the weld. Summary of the Invention
[0004] The purpose of this invention is to address the aforementioned problems in existing technologies by proposing a process method for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] A process for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding includes the following steps:
[0007] S1. Fix the aluminum-aluminum lap joint to the welding fixture, and uniformly coat the lap joint interface with a composite flux of 0.1-0.3mm thickness. The aluminum-aluminum lap joint is a hard aluminum alloy lap joint or a soft aluminum alloy lap joint. The flux can form a uniform diffusion layer during the welding process and promote the diffusion bonding between atoms.
[0008] S2. Polymer diffusion welding is carried out in a hot pressing equipment at a temperature of 550-630℃ and a pressure of 1-5MPa, with a holding time of 30-70s. During the hot pressing process, the polymer diffusion flux undergoes a chemical reaction under high temperature and high pressure to form a stable diffusion layer, enabling the two welded parts to achieve a tight bond at the atomic level, thereby solving the gap problem between the welded parts.
[0009] S3. Allow the material to cool naturally to room temperature to complete the polymer diffusion welding process. Inspect the aluminum-aluminum lap joints after polymer diffusion welding to ensure that there are no obvious defects in the welded parts.
[0010] S4. Use a handheld laser welding device to perform reinforcement welding along the lap joint interface. The laser power is 1000-2000W, the welding speed is 3-5mm / s, and the spot diameter is 2-3mm. Simultaneously feed Al-Cu-Mn-Sc alloy welding wire. During the welding process, the laser beam is focused on the welding area to form a high-energy-density heat source, which makes the surface of the workpiece melt rapidly. At the same time, welding rods are added to achieve rapid melting and connection of materials.
[0011] S5. Dynamically adjust the laser power based on the real-time contact resistance value. When R > 20μΩ, increase the power to 105-110% of the set value; when R < 10μΩ, decrease the power to 90-95%.
[0012] S6. Polish the welded parts to remove unevenness and burrs from the weld surface and improve the appearance quality of the welded parts.
[0013] S7. Conduct quality inspection on the welded aluminum-aluminum lap joints.
[0014] By combining diffusion welding and laser welding, porosity / lack of fusion defects at the hard aluminum lap joint interface are eliminated. Dynamic intelligent control and real-time resistance feedback reduce the welding defect rate and ensure the safety of high-current components in electric vehicles.
[0015] Preferably, in step S1, the composite flux comprises the following components and mass percentages:
[0016] The nano-SiO2@Ag core-shell particles account for 55-65%, of which the Ag shell thickness is 20-50nm and the SiO2 core diameter is 60-150nm;
[0017] Bi2O3-SnTe eutectic powder 18-22%, wherein the molar ratio of Bi2O3 to SnTe is 1:(0.8-1.2), and the particle size is 1-5μm;
[0018] The remainder is a polyvinylpyrrolidone / ethanol solution carrier.
[0019] SiO2@Ag (Ag shell 20-50nm) forms a continuous conductive network at 550-630℃, which facilitates the reduction of interfacial resistance. Bi2O3-SnTe eutectic powder precisely breaks the Al2O3 oxide film at 580℃, which facilitates the improvement of diffusion bonding strength. Polyvinylpyrrolidone / ethanol solution ensures uniform flux coating with thickness fluctuation ≤±0.03mm.
[0020] Preferably, the mass ratio of Ag in the nano-SiO2@Ag core-shell particles is 58-62%, which helps to balance conductivity and cost and avoids interface embrittlement caused by excessive Ag; and the particle surface is modified by silane coupling agent KH-550, which helps to enhance the interfacial bonding force between the nanoparticles and the aluminum matrix, thereby improving the uniformity of the Ag2Al diffusion layer thickness.
[0021] Preferably, in step S4, the composition of the Al-Cu-Mn-Sc alloy welding wire, by mass percentage, is:
[0022] Cu 5.0-6.0%, Mn 0.7-0.9%, Sc 0.25-0.35%, Fe≤0.2%, Si≤0.15%, balance Al, welding wire diameter 1.0-1.2mm.
[0023] Preferably, in step S4, the laser welding spot adopts dynamic zoom control, with the defocusing amount at the welding start end being +1.5mm to +2mm to facilitate the suppression of spatter, and the defocusing amount at the welding end being -0.5mm to 0mm to ensure fusion. The spot diameter fluctuation throughout the process is ≤0.3mm, which facilitates the enhancement of weld width consistency.
[0024] Preferably, in step S5, the real-time contact resistance detection adopts a four-terminal method with a sampling frequency ≥100Hz to prevent local non-fusion, and the power adjustment response time ≤200ms to avoid batch scrap and reduce the energy consumption of a single unit.
[0025] Preferably, the method for preparing the composite flux includes:
[0026] Nano-SiO2@Ag particles and Bi2O3-SnTe eutectic powder are ball-milled and mixed under argon protection for 2-4 hours to prevent nano-Ag oxidation and improve flux activity retention. The mixture is then dispersed in an ethanol solution containing 5wt% polyvinylpyrrolidone and ultrasonically vibrated for 30-60 minutes to form a uniform slurry, ensuring uniform distribution of core-shell particles.
[0027] Preferably, in step S4, the reinforcing welding path is an overlapping double-pass welding. The first pass welding line energy is 80-120 J / mm to thoroughly remove residual oxides at the diffusion welding interface. The second pass welding line energy is 60-90 J / mm to repair surface pits. The overlap rate of the two passes is 40-50% to eliminate the weakening of the heat-affected zone between weld passes.
[0028] Preferably, during natural cooling in step S3, the cooling rate is controlled to be ≤5℃ / s within the temperature range of 100-250℃ to suppress the quenching stress of hard aluminum near 200℃ and reduce the occurrence rate of cold cracks.
[0029] Preferably, in step S7, the quality inspection includes:
[0030] The contact resistance of the welded aluminum-aluminum lap joints was tested, and the contact resistance was ≤40μΩ;
[0031] Temperature rise test of the welded aluminum-aluminum lap joints, temperature rise ≤30K;
[0032] A tensile test was performed on the welded aluminum-aluminum lap joints, and the tensile force value was ≥800N.
[0033] Compared with existing technologies, this process for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding has the following advantages:
[0034] 1. The present invention provides a process method for welding aluminum-aluminum lap joints by combining polymer diffusion welding and handheld laser welding. By combining polymer diffusion welding and handheld laser welding, the gap problem and durability problem existing in the welding of aluminum-aluminum lap joints are effectively solved.
[0035] 2. The present invention provides a process method for welding aluminum-aluminum lap joints by combining polymer diffusion welding and handheld laser welding. By forming a continuous conductive network at the interface through nano-SiO2@Ag core-shell flux, combined with dynamic resistance control, the contact resistance is significantly reduced.
[0036] 3. The present invention provides a process method for welding aluminum-aluminum lap joints by combining polymer diffusion welding and handheld laser welding. By using micro-alloy welding wire laser reinforcement to refine the weld grains, and with the energy gradient distribution of double-pass welding, the tensile strength of hard aluminum-hard aluminum lap joints is ≥2000N.
[0037] 4. The present invention provides a process method for welding aluminum-aluminum lap joints by combining polymer diffusion welding and handheld laser welding. Based on real-time contact resistance feedback, the laser power is dynamically adjusted to reduce heat input fluctuations, avoid local overheating or lack of fusion, and improve the mass production qualification rate.
[0038] In summary, this invention provides a process for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding. By constructing an atomic-level conductive path through a nano-Ag diffusion layer, achieving strong interfacial connections through microalloy laser reinforcement, and ensuring process consistency through dynamic closed-loop control, this invention effectively solves the gap and durability problems existing in the welding of aluminum-aluminum lap joints. Ultimately, it simultaneously achieves low resistance, high strength, excellent fatigue resistance, and low-temperature stability on aluminum alloy lap joints, synergistically optimizing the conductivity, mechanical properties, and durability of high-strength aluminum alloy connections. Attached Figure Description
[0039] Figure 1 This is a comparison diagram of the effects before and after joint welding in Specific Embodiment 1.
[0040] Figure 2 The figure shows the temperature rise test results in specific embodiment two.
[0041] Figure 3 , Figure 4 , Figure 5 These are curves a, b, and c from the test results, respectively. Detailed Implementation
[0042] The following are specific embodiments of the present invention, which are described in conjunction with the accompanying drawings. However, the present invention is not limited to these embodiments. Specific Implementation Example 1:
[0044] A process for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding includes the following steps:
[0045] S1. Fix the aluminum-aluminum lap joint to the welding fixture, and uniformly apply a 0.1-0.3mm thick composite flux to the lap joint interface. The aluminum-aluminum lap joint is a hard aluminum alloy lap joint. The composite flux includes the following components and mass percentages:
[0046] The nano-SiO2@Ag core-shell particles account for 55-65%, of which the Ag shell thickness is 20-50nm and the SiO2 core diameter is 60-150nm;
[0047] Bi2O3-SnTe eutectic powder 18-22%, wherein the molar ratio of Bi2O3 to SnTe is 1:(0.8-1.2), and the particle size is 1-5μm;
[0048] The remainder is a polyvinylpyrrolidone / ethanol solution carrier.
[0049] Among them, the mass ratio of Ag in the nano SiO2@Ag core-shell particles is 58-62%, and the particle surface is modified by silane coupling agent KH-550.
[0050] S2. Perform polymer diffusion welding in a hot press equipment at a temperature of 550-630℃ and a pressure of 1-5MPa, with a holding time of 30-70s.
[0051] S3. Allow natural cooling to room temperature, with a cooling rate controlled at ≤5℃ / s within the temperature range of 100-250℃.
[0052] S4. Use a handheld laser welding device to perform reinforcement welding along the lap joint interface. The laser power is 1000-2000W, the welding speed is 3-5mm / s, and the spot diameter is 2-3mm. Simultaneously feed Al-Cu-Mn-Sc alloy welding wire. The composition of the Al-Cu-Mn-Sc alloy welding wire, by mass percentage, is: Cu 5.0-6.0%, Mn 0.7-0.9%, Sc 0.25-0.35%, Fe≤0.2%, Si≤0.15%, with the balance being Al. The welding wire diameter is 1.0-1.2mm. The laser welding spot adopts dynamic zoom control. The defocusing amount at the welding start end is +1.5mm to +2mm, and the defocusing amount at the welding end is -0.5mm to 0mm. The spot diameter fluctuation throughout the process is ≤0.3mm. The reinforcement welding path is an overlapping double-pass welding. The first welding line energy is 80-120J / mm, the second welding line energy is 60-90J / mm, and the overlap rate of the two passes is 40-50%.
[0053] S5. The laser power is dynamically adjusted based on the real-time contact resistance value. When R > 20μΩ, the power is increased to 105-110% of the set value, and when R < 10μΩ, it is reduced to 90-95%. The real-time contact resistance detection adopts the four-terminal method, the sampling frequency is ≥100Hz, and the power adjustment response time is ≤200ms.
[0054] S6. Polish the welded area to remove unevenness and burrs from the weld surface;
[0055] S7. Conduct quality inspection on the welded aluminum-aluminum lap joints. Specific Implementation Example 2:
[0057] Specific embodiment two involves performing a temperature rise test on the aluminum-aluminum lap joint welded using a combination of polymer diffusion welding and handheld laser welding as described in specific embodiment one. The specific steps are as follows:
[0058] According to the first step of the specific embodiment, a hard aluminum 6061-T6 lap joint specimen was prepared with dimensions of 100mm × 30mm × 2mm and an lap area of 100mm². 2The device uses a DC regulated power supply (accuracy ±0.5%) with an output of 140A±1A. The temperature measuring device uses a type K thermocouple (accuracy ±0.5℃), which is attached to the center point of the overlap interface. The environment is a constant temperature laboratory at 25℃±1℃ with no forced convection. The device is powered on continuously for 1 hour, and the temperature is recorded every second, in accordance with GB / T 2423.22-2012 "Environmental Testing for Electrical and Electronic Products - Part 2: Test Methods - Test N: Temperature Change".
[0059] Test Procedure: First, install the test piece by clamping both ends of the welded lap joint onto the copper electrode fixture and applying conductive paste to the contact surface to reduce contact resistance. Then, fix the thermocouple by using high-temperature tape to tightly adhere the thermocouple measuring point to the center of the lap joint interface to ensure the shortest heat conduction path. Next, apply a 140A DC current and start timing to collect temperature data in real time. Test three test pieces (three welded lap joints) and the judgment criterion is ΔT ≤ 30K.
[0060] Figure 2 The test results of this embodiment are shown. Figure 3 , Figure 4 , Figure 5 Curves a, b, and c from the test results are shown respectively. These three curves describe the surface heating of the three welded lap joints under rated current conditions. The test duration was one hour (3600 seconds). Based on the 140A continuous current temperature rise test results, it can be seen that the measured temperature rise of specimens 1#~3# is significantly lower than the ≤30K limit. This process forms a highly efficient conductive network through a nano-Ag diffusion layer, which significantly reduces Joule heating compared to traditional processes. Combined with the excellent thermal conductivity of the hard aluminum substrate and the dense interface of laser welding, heat is rapidly and evenly distributed. In the connection of power battery modules, it can ensure that the temperature difference between cells is <2℃, extending the battery cycle life to more than 2000 cycles. At the same time, it improves the safety margin compared with ultrasonic welding / riveting solutions, providing a highly reliable, long-life, and maintenance-free connection solution for the three-electric system of electric vehicles. Specific Implementation Example 3:
[0062] A process for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding includes the following steps:
[0063] S1. Fix the aluminum-aluminum lap joint to the welding fixture, and uniformly apply a 0.1-0.3mm thick composite flux to the lap joint interface. The aluminum-aluminum lap joint is a lap joint of soft aluminum alloy and hard aluminum alloy. The composite flux includes the following components and mass percentages:
[0064] The nano-SiO2@Ag core-shell particles account for 55-65%, of which the Ag shell thickness is 20-50nm and the SiO2 core diameter is 60-150nm;
[0065] Bi2O3-SnTe eutectic powder 18-22%, wherein the molar ratio of Bi2O3 to SnTe is 1:(0.8-1.2), and the particle size is 1-5μm;
[0066] The remainder is a polyvinylpyrrolidone / ethanol solution carrier.
[0067] Among them, the mass ratio of Ag in the nano SiO2@Ag core-shell particles is 58-62%, and the particle surface is modified by silane coupling agent KH-550.
[0068] S2. Perform polymer diffusion welding in a hot press equipment at a temperature of 550-630℃ and a pressure of 1-5MPa, with a holding time of 30-70s.
[0069] S3. Allow natural cooling to room temperature, with a cooling rate controlled at ≤5℃ / s within the temperature range of 100-250℃.
[0070] S4. Use a handheld laser welding device to perform reinforcement welding along the lap joint interface. The laser power is 1000-2000W, the welding speed is 3-5mm / s, and the spot diameter is 2-3mm. Simultaneously feed Al-Cu-Mn-Sc alloy welding wire. The composition of the Al-Cu-Mn-Sc alloy welding wire, by mass percentage, is: Cu 5.0-6.0%, Mn 0.7-0.9%, Sc 0.25-0.35%, Fe≤0.2%, Si≤0.15%, with the balance being Al. The welding wire diameter is 1.0-1.2mm. The laser welding spot adopts dynamic zoom control. The defocusing amount at the welding start end is +1.5mm to +2mm, and the defocusing amount at the welding end is -0.5mm to 0mm. The spot diameter fluctuation throughout the process is ≤0.3mm. The reinforcement welding path is an overlapping double-pass welding. The first welding line energy is 80-120J / mm, the second welding line energy is 60-90J / mm, and the overlap rate of the two passes is 40-50%.
[0071] S5. The laser power is dynamically adjusted based on the real-time contact resistance value. When R > 20μΩ, the power is increased to 105-110% of the set value, and when R < 10μΩ, it is reduced to 90-95%. The real-time contact resistance detection adopts the four-terminal method, the sampling frequency is ≥100Hz, and the power adjustment response time is ≤200ms.
[0072] S6. Polish the welded area to remove unevenness and burrs from the weld surface;
[0073] S7. Conduct quality inspection on the welded aluminum-aluminum lap joints. Specific Implementation Example 4:
[0075] Specific embodiment four involves preparing aluminum-aluminum lap joints using a combined welding method as described in specific embodiments one and three, and conducting tensile tests on the lap joints. The difference is that specific embodiment one uses hard aluminum lap joints with hard aluminum, while specific embodiment three uses soft aluminum lap joints with hard aluminum. The specific steps for the tensile test are as follows:
[0076] S1. Fix the aluminum-aluminum lap joint to the welding fixture, and uniformly apply a 0.1-0.3mm thick composite flux to the lap joint interface. The aluminum-aluminum lap joint is either a hard aluminum alloy to hard aluminum alloy lap or a soft aluminum alloy to hard aluminum alloy lap. The composite flux includes the following components and their mass percentages:
[0077] The nano-SiO2@Ag core-shell particles account for 55-65%, of which the Ag shell thickness is 20-50nm and the SiO2 core diameter is 60-150nm;
[0078] Bi2O3-SnTe eutectic powder 18-22%, wherein the molar ratio of Bi2O3 to SnTe is 1:(0.8-1.2), and the particle size is 1-5μm;
[0079] The remainder is a polyvinylpyrrolidone / ethanol solution carrier.
[0080] Among them, the mass ratio of Ag in the nano SiO2@Ag core-shell particles is 58-62%, and the particle surface is modified by silane coupling agent KH-550.
[0081] S2. Perform polymer diffusion welding in a hot press equipment at a temperature of 550-630℃ and a pressure of 1-5MPa, with a holding time of 30-70s.
[0082] S3. Allow natural cooling to room temperature, with a cooling rate controlled at ≤5℃ / s within the temperature range of 100-250℃.
[0083] S4. Use a handheld laser welding device to perform reinforcement welding along the lap joint interface. The laser power is 1000-2000W, the welding speed is 3-5mm / s, and the spot diameter is 2-3mm. Simultaneously feed Al-Cu-Mn-Sc alloy welding wire. The composition of the Al-Cu-Mn-Sc alloy welding wire, by mass percentage, is: Cu 5.0-6.0%, Mn 0.7-0.9%, Sc 0.25-0.35%, Fe≤0.2%, Si≤0.15%, with the balance being Al. The welding wire diameter is 1.0-1.2mm. The laser welding spot adopts dynamic zoom control. The defocusing amount at the welding start end is +1.5mm to +2mm, and the defocusing amount at the welding end is -0.5mm to 0mm. The spot diameter fluctuation throughout the process is ≤0.3mm. The reinforcement welding path is an overlapping double-pass welding. The first welding line energy is 80-120J / mm, the second welding line energy is 60-90J / mm, and the overlap rate of the two passes is 40-50%.
[0084] S5. The laser power is dynamically adjusted based on the real-time contact resistance value. When R > 20μΩ, the power is increased to 105-110% of the set value, and when R < 10μΩ, it is reduced to 90-95%. The real-time contact resistance detection adopts the four-terminal method, the sampling frequency is ≥100Hz, and the power adjustment response time is ≤200ms.
[0085] S6. Polish the welded area to remove unevenness and burrs from the weld surface;
[0086] S7. Conduct quality inspection on the welded aluminum-aluminum lap joints.
[0087] The hard aluminum used was 6061-T6, with dimensions of 100×30×2 mm, and the soft aluminum used was 1060-O, also with dimensions of 100×30×2 mm. A universal testing machine (accuracy ±0.5%FS, range ≥10 kN) was used. The two ends of the lap joint were clamped in fixtures with a clamping length ≥15 mm. The ball joint was adjusted to align the specimen axis with the tensile direction. A preload of 50 N was applied to eliminate clamping gaps. An extensometer was installed 10 mm outside the lap area (to monitor base material deformation). The formal test involved tensile testing at a constant rate of 2 mm / min. The load-displacement curve was monitored in real time until fracture. The maximum fracture load Fmax (N) was recorded. Each sample underwent three tests.
[0088] Table 1 Tensile Test Results
[0089]
[0090] As shown in the table above, the lap strength of hard aluminum-hard aluminum is far greater than that of the base material, which meets the vibration and impact resistance requirements of electric vehicle battery modules. The soft aluminum-hard aluminum combination is suitable for non-load-bearing conductive components because the yield strength of soft aluminum is insufficient.
[0091] Comparative Example 1:
[0092] S1. Fix the aluminum-aluminum lap joint to the welding fixture, and uniformly apply a 0.1-0.3mm thick composite flux to the lap joint interface. The aluminum-aluminum lap joint is a hard aluminum alloy lap joint. The composite flux includes the following components and mass percentages:
[0093] The nano-SiO2@Ag core-shell particles account for 55-65%, of which the Ag shell thickness is 20-50nm and the SiO2 core diameter is 60-150nm;
[0094] Bi2O3-SnTe eutectic powder 18-22%, wherein the molar ratio of Bi2O3 to SnTe is 1:(0.8-1.2), and the particle size is 1-5μm;
[0095] The remainder is a polyvinylpyrrolidone / ethanol solution carrier.
[0096] Among them, the mass ratio of Ag in the nano SiO2@Ag core-shell particles is 58-62%, and the particle surface is modified by silane coupling agent KH-550.
[0097] S2. Perform polymer diffusion welding in a hot press equipment at a temperature of 550-630℃ and a pressure of 1-5MPa, with a holding time of 30-70s.
[0098] S3. Allow natural cooling to room temperature, with a cooling rate controlled at ≤5℃ / s within the temperature range of 100-250℃.
[0099] S4. Polish the welded area to remove unevenness and burrs from the weld surface;
[0100] S5. Conduct quality inspection on the welded aluminum-aluminum lap joints.
[0101] Comparative Example 2:
[0102] S1. Use a handheld laser welding device to weld along the lap joint (overlap of hard aluminum alloys). The laser power is 1000-2000W, the welding speed is 3-5mm / s, and the spot diameter is 2-3mm. Simultaneously feed Al-Cu-Mn-Sc alloy welding wire. The composition of the Al-Cu-Mn-Sc alloy welding wire, by mass percentage, is: Cu 5.0-6.0%, Mn 0.7-0.9%, Sc 0.25-0.35%, Fe≤0.2%, Si≤0.15%, balance Al, welding wire diameter 1.0-1.2mm; the laser welding spot adopts dynamic zoom control, the defocusing amount at the welding start end is +1.5mm to +2mm, the defocusing amount at the welding end is -0.5mm to 0mm, and the spot diameter fluctuation throughout the process is ≤0.3mm; the reinforcement welding path is an overlapping double-pass welding, the first welding line energy is 80-120J / mm, the second welding line energy is 60-90J / mm, and the overlap rate of the two passes is 40-50%.
[0103] S2. Polish the welded area to remove unevenness and burrs from the weld surface;
[0104] S3. Conduct quality inspection on the welded aluminum-aluminum lap joints. Specific Implementation Example 5:
[0106] Samples were prepared using the methods described in Specific Example 1, Specific Example 3, Comparative Example 1, and Comparative Example 2, and contact resistance and fatigue life tests were performed. The overlap area was 100 mm². 2The flux thickness is 0.2mm. Contact resistance test: According to GB / T6146-2010 standard, the initial contact resistance of four groups of specimens was measured using the Kelvin four-terminal method at 25℃ and 100A DC current. Fatigue life test: According to ISO 12106:2017 standard, an axial tensile-tensile load (stress amplitude Δσ=120 MPa, stress ratio R=0.1, frequency 15Hz) was applied using a hydraulic servo fatigue testing machine, cyclically until the specimen fractured or reached 10 cycles. 6 The circuit is stopped once, and the resistance change is monitored in real time, and the number of fracture cycles and failure modes are recorded.
[0107] Table 2 Key Performance Comparison Table
[0108]
[0109] As shown in the table above, Specific Embodiment 1 (hard aluminum lapped with hard aluminum) and Specific Embodiment 3 (soft aluminum lapped with hard aluminum) exhibit superior overall performance compared to Comparative Embodiment 1 and Comparative Embodiment 2, thanks to the continuous conductive network formed by the nano-Ag diffusion layer and the interface gradient structure imparted by the Sc microalloy laser reinforcement. The combined application of polymer diffusion welding and handheld laser welding effectively solves the gap and durability problems existing in the welding of aluminum-aluminum lap joints. Polymer diffusion welding forms a stable diffusion layer during the welding process, enabling the weldment to bond tightly at the atomic level, improving the conductivity and durability of the welded area. Handheld laser welding reinforces the welded area, further improving the weld strength and preventing weldment detachment. Through the process method of this invention, the welding quality is significantly improved, meeting customer requirements for product performance and reliability.
[0110] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.
Claims
1. A process for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding, characterized in that, Includes the following steps: S1. Fix the aluminum-aluminum lap joint to the welding fixture, and uniformly coat the lap joint interface with a composite flux of 0.1-0.3 mm thickness. The aluminum-aluminum lap joint is a hard aluminum alloy lap joint or a soft aluminum alloy lap joint. The composite flux includes the following components and mass percentages: 55-65% nano-SiO2@Ag core-shell particles, wherein the Ag shell thickness is 20-50 nm and the SiO2 core diameter is 60-150 nm; 18-22% Bi2O3-SnTe eutectic powder, wherein the molar ratio of Bi2O3 to SnTe is 1:(0.8-1.2) and the particle size is 1-5 μm; the balance is a polyvinylpyrrolidone / ethanol solution carrier. S2. Perform polymer diffusion welding in a hot press equipment at a temperature of 550-630℃ and a pressure of 1-5MPa, with a holding time of 30-70s. S3. Allow to cool naturally to room temperature; S4. Use a handheld laser welding device to reinforce the lap joint with a laser power of 1000-2000W, a welding speed of 3-5mm / s, a spot diameter of 2-3mm, and simultaneously feed Al-Cu-Mn-Sc alloy welding wire. S5. Dynamically adjust the laser power based on the real-time contact resistance value. When R > 20μΩ, increase the power to 105-110% of the set value; when R < 10μΩ, decrease the power to 90-95%. S6. Polish the welded area to remove unevenness and burrs from the weld surface; S7. Conduct quality inspection on the welded aluminum-aluminum lap joints.
2. The process method for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding as described in claim 1, characterized in that, The mass percentage of Ag in the nano-SiO2@Ag core-shell particles is 58-62%, and the particle surface is modified with silane coupling agent KH-550.
3. The process method for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding as described in claim 1, characterized in that... In step S4, the composition of the Al-Cu-Mn-Sc alloy welding wire, by mass percentage, is: Cu 5.0-6.0%, Mn 0.7-0.9%, Sc 0.25-0.35%, Fe≤0.2%, Si≤0.15%, balance Al, welding wire diameter 1.0-1.2mm.
4. The process method for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding as described in claim 1, characterized in that, In step S4, the laser welding spot is dynamically zoomed, with the defocusing amount at the welding start end being +1.5mm to +2mm and the defocusing amount at the welding end being -0.5mm to 0mm, and the spot diameter fluctuation throughout the process being ≤0.3mm.
5. The process method for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding as described in claim 1, characterized in that, In step S5, the real-time contact resistance detection adopts the four-terminal method, with a sampling frequency ≥100Hz and a power adjustment response time ≤200ms.
6. The process method for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding as described in claim 1, characterized in that, The preparation method of the composite flux includes: Nano-SiO2@Ag particles and Bi2O3-SnTe eutectic powder were ball-milled and mixed under argon protection for 2-4 hours, then dispersed in an ethanol solution containing 5wt% polyvinylpyrrolidone, and ultrasonically vibrated for 30-60 minutes to form a uniform slurry.
7. The process method for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding as described in claim 1, characterized in that, In step S4, the reinforcement welding path is an overlapping double-pass welding, with the first welding line energy being 80-120 J / mm and the second welding line energy being 60-90 J / mm, and the overlap rate between the two passes being 40-50%.
8. The process method for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding as described in claim 1, characterized in that, During natural cooling in step S3, the cooling rate is controlled to be ≤5℃ / s within the temperature range of 100-250℃.
9. The process method for welding aluminum-aluminum lap joints using a combination of polymer diffusion welding and handheld laser welding as described in claim 1, characterized in that, In step S7, the quality inspection includes: The contact resistance of the welded aluminum-aluminum lap joints was tested, and the contact resistance was ≤40μΩ; Temperature rise test of the welded aluminum-aluminum lap joints, temperature rise ≤30K; A tensile test was performed on the welded aluminum-aluminum lap joints, and the tensile force value was ≥800N.
Citation Information
Patent Citations
Method for connecting aluminum alloy and steel by laser filler wire
CN101941119A
Welding method for diffusion welding of aluminum-lithium alloy
CN114043063A